Synthesis of MnNiO3/Mn3O4 Nanocomposites for Water Electrolysis Process - Rathika, S.; Rathika, S.; Ravi, G.; Yuvakkumar, R. (University of Jaffna, 2019)
Hydrothermal method was optimized to produce highly efficient, novel MnNiO3/Mn3O4 nanocomposites for water electrolysis process. The predominant peak observed at 36.6o corresponds to the X-ray crystal plane orientation of (1-10) and confirmed Rhombohedral phase MnNiO3 and other well resolved peaks attributed to the MnNiO3/Mn3O4 nanocomposites. Vibrational properties and metal oxygen vibration present in Fourier transform infrared profile around ~570-620 cm-1. The oxygen vacancies and electron trapping mechanism were revealed from photoluminescence spectra. The combined morphology of nanorods and distinguished nanopetals was achieved for highly active MnNiO3 nanocatalyst. The band structure and modification was thoroughly studied by UV visible diffuse reflection spectroscopy and the observed band gap was 2.8 eV for MnNiO3/Mn3O4 nanocomposites. Cyclic voltammogram and linear sweep voltammogram studies investigated the redox behaviour and water oxidation nature of the novel MnNiO3/Mn3O4 nanocomposites. The excellent conductivity and ionic mobility were confirmed by electrochemical impedance spectroscopy. Long-time durability of 24 h stability test was carried out and reported for the optimized electrocatalyst. Hence, the present study completely dealt with the preparation of novel combination of MnNiO3/Mn3O4 nanocomposites using controlled synthesis technique and the exploration of optimized candidate for efficient water electrolysis process
Keywords: Novel MnNiO3/Mn3O4; Nanorods-distinguished nanopetals; Water electrolysis process